Preoperative planning of gluteoplasty and Brazilian Butt Lift (BBL): Some considerations on the aesthetics of female buttocks - Raposio, Edoardo; Baldelli, Ilaria (Acta Biomedica Atenei Parmensis, 2025)
Modern cosmetic surgery has seen an increase in demand for gluteal enhancement procedures, reflecting an evolution in beauty standards. This paper reviews some aesthetic ideals and beauty characteristics associated with the female buttocks, examining key attributes of the buttocks that contribute to an ideal appearance, including volume, shape, and proportions. An understanding of these characteristics is essential for clinicians in aesthetic gluteal surgery to meet patient expectations and achieve visually pleasing outcomes.